ACE-Informed Responses in Central Texas: Findings from a Needs Assessment. Issue 7 (17th November 2021) - Gerlach, Beth; LaBrenz, Catherine A.; Barczyk, Amanda N.; Larkin, Heather; Van Diest, Heather; Morris, Marian; Faulkner, Monica
ABSTRACT: The objectives of this study were to examine: a) adverse childhood experience (ACE) knowledge among healthcare professionals in Central Texas; b) prevalence of screening and patient disclosure of ACEs; c) implementation of ACE-informed response strategies; and d) the relationship between ACE knowledge and familiarity, and implementation of ACE-informed response strategies. A needs assessment was conducted using an online survey that included closed- and open-ended questions. Purposive and snowball sampling were utilized to recruit healthcare providers, with a focus on pediatric and women's healthcare providers. Eighty-five healthcare providers completed the survey. Most respondents were unfamiliar with the ACE study, but 59.6% had attended trainings on the impact of trauma on child health. Respondents screened most frequently for mental illness and drug/alcohol abuse in their practice. The most frequently reported ACE-informed response strategies included identifying strengths and utilizing on-site resources, while broader strategies such as creating an ACE-informed culture within their practice were implemented by less than 10% of respondents. ACE knowledge was correlated with two of the ACE-informed response strategies. Although many healthcare providers still lack familiarity with ACEs, awareness of trauma and its impact on child health may be more common. Given the positive correlation between ACE familiarity and ACE-informed response strategies, it appears more education and resources are needed to engage healthcare providers in responding to ACEs. Specific strategies, such as community-wide trainings, opportunities for provider collaboration and communication, and critical analysis of policies, may cultivate a more ACE-informed and ACE-responsive culture.